2011
DOI: 10.1016/j.ijgo.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the persistence of stress urinary incontinence from pregnancy to 2 years post partum

Abstract: Higher BMI in pregnant women at term was an independent risk factor for the persistence of SUI from pregnancy to 2 years post partum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
6
12
0
Order By: Relevance
“…In contrast to previous studies that assessed BP and UI either retrospectively or in distinct populations such as nulliparas, the present study analysed the prevalence and the characteristics of these symptoms in a pregnant population of primi- and multiparas drawn from a prospective, community-based pregnancy cohort representing a metropolitan population who received prenatal care in community clinics and obstetrical care for labour and at delivery in tertiary hospitals. In agreement with previous studies, our findings also support a high prevalence of BP during the postpartum period [28, 35]. Furthermore, the proportion of women affected by BP and the impairment of maternal performance of daily tasks due to BP has a higher impact on women’s health and performance of daily tasks at 12 months postpartum than that by UI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to previous studies that assessed BP and UI either retrospectively or in distinct populations such as nulliparas, the present study analysed the prevalence and the characteristics of these symptoms in a pregnant population of primi- and multiparas drawn from a prospective, community-based pregnancy cohort representing a metropolitan population who received prenatal care in community clinics and obstetrical care for labour and at delivery in tertiary hospitals. In agreement with previous studies, our findings also support a high prevalence of BP during the postpartum period [28, 35]. Furthermore, the proportion of women affected by BP and the impairment of maternal performance of daily tasks due to BP has a higher impact on women’s health and performance of daily tasks at 12 months postpartum than that by UI.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies report lower prevalence of UI in the late postpartum period, around 12% in a study by Burgio et al (2003) [33] and 24% by Woolhouse et al [26]. The findings from this study are similar to more recent reports on postpartum incontinence that also report higher UI prevalence at 12 months postpartum [34, 35]. In contrast to previous studies that assessed BP and UI either retrospectively or in distinct populations such as nulliparas, the present study analysed the prevalence and the characteristics of these symptoms in a pregnant population of primi- and multiparas drawn from a prospective, community-based pregnancy cohort representing a metropolitan population who received prenatal care in community clinics and obstetrical care for labour and at delivery in tertiary hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…It appears that a woman must have all children delivered by cesarean section in order to achieve protection against long-term incontinence 35 . Urinary incontinence in pregnancy increases the risk of later urinary incontinence, both postpartum and later in life 17,38 , but nevertheless it is not a predictor of benefi t from giving birth by cesarean section to protect against urine leakage 17,39 . Increase of urethral mobility in combination with lesions of the levator ani muscle is the probable mechanism of impairment during vaginal delivery 40 .…”
Section: Impact Of Pregnancy and Delivery On Urinary Incontinencementioning
confidence: 99%
“…27 Mode of delivery and parity is considered as factors contributing towards worsening of urinary incontinence. [28][29][30][31] It is well known that the vaginal delivery generates neurologic changes that affect the Urethra; these changes seem to be less pronounced in cases of caesarian section (C/section), 32,33 giving c/section a protective role against UI. A Chinese study 34 on primipara who delivered either vaginal way or by c/section concluded a high occurrence of UI in the vaginal birth group than in the Caesarian section group; it also suggested that vaginal delivery, lateral episiotomy and new born weight (over 4000 g) were risk factor of postpartum UI and pelvic Organ prolapse.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%